TBMM MÜZAKERELERİNDE ORTAYA KOYDUĞU DÜŞÜNCE VE FİKİRLERİ İLE EĞİTİMCİ BİR MİLLETVEKİLİ: İSMAİL HAKKI BALTACIOĞLU - Yaşar ÖZÜÇETİN; Mustafa MUTLU (International Journal of Eurasia Social Sciences, 2016)
İsmail Hakkı Baltacıoğlu, who took place in the Assembly as Republican People’s Party (CHP) VII. Term Afyonkarahisar parliament member and VIII. Term Kırşehir parliament member, is a prominent character for his resolution in fighting, an intellectual man of education and politics who dedicated himself to his country and who, during the time of his membership, with his statements, motions, proposals and words, presented his thoughts and opinions about various issues in General Assemblies as such;One becomes a European in respect of abiding by its institutions, culture, civilization and human rights and freedoms, what entering into EU means is not just a matter of geography but being a civilized nation; though orientation of the main politics is to be toward West Europe, interest in Near East and Asia should never diminish but in fact it is to grow stronger,Like in all over the world, our country also has the problem of a non-humanitarian and non-scientific examination system, by assessing the memory, this does not look for power but only memorizing, what nationals need is not memorizing people but creative people who transform their knowledge into practice, people should be a little adaptable to arts and techniques of the country, location they live in, raising moral youth with strong character who are patriotic and bound to their nation and its values cannot be ensured by providing courses under title ethics in schools, personality of a person is formed with all affective elements of education in a school and daily matters which are considered to be little,We should get rid of unnecessary information, schools must be turned into homes of ethics and democracy and ethical formation will occur necessarily with the effect of life, law, rules and traditions,Sculptors and painters must be supported on the one hand and subject to tax on the other hand.